2022
DOI: 10.1002/ird.2757
|View full text |Cite
|
Sign up to set email alerts
|

Development of a smart IoT‐based drip irrigation system for precision farming

Abstract: Precision irrigation scheduling using real-time sensors has the potential to boost water use efficiency while maximizing resource utilization. Traditional farming is adversely affected by improper resource management. To overcome a farmer's efforts, an IoT-based drip irrigation system was developed and tested for system performance. It was compared with an ETc-based drip irrigation system for brinjal crops grown in planter beds filled with vertisols. The developed system, consisting of sensors and microcontrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The field data collection system contains three sensors: a capacitive soil moisture sensor (v2.0), a soil temperature sensor (DS18B20), and a temperature and humidity sensor (DHT11). The output of this sensor is read by an ESP32-WROOM-32 microcontroller, which wirelessly transmits the recorded data to an IoT platform (ThingSpeak) using an ESP8266 Wi-Fi module (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). Details of the development of IoT-based smart drip irrigation systems are described in (Kumar et al 2022;Kumar et al 2023), and a flowchart of the process is shown in (Fig.…”
Section: Iot-based Data Acquisition Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The field data collection system contains three sensors: a capacitive soil moisture sensor (v2.0), a soil temperature sensor (DS18B20), and a temperature and humidity sensor (DHT11). The output of this sensor is read by an ESP32-WROOM-32 microcontroller, which wirelessly transmits the recorded data to an IoT platform (ThingSpeak) using an ESP8266 Wi-Fi module (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). Details of the development of IoT-based smart drip irrigation systems are described in (Kumar et al 2022;Kumar et al 2023), and a flowchart of the process is shown in (Fig.…”
Section: Iot-based Data Acquisition Systemmentioning
confidence: 99%
“…Due to the wiring connection range, such systems have a limited deployment size for monitoring points; they require extensive cabling, which leads to high installation, maintenance, and relocation costs; and the cables are easily damaged if placed outdoors in adverse conditions (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). In the present research work, we have developed an IoT system that uses wireless sensor networks (WSNs) technology to overcome previous wired sensor system issues.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2023) presented a novel IoT‐based drip irrigation system designed for precision farming. The study addressed the need for efficient and precise water management in agriculture.…”
Section: Introductionmentioning
confidence: 99%